2022
DOI: 10.1007/s11010-022-04473-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigating microRNAs in diabetic cardiomyopathy as tools for early detection and therapeutics

Abstract: To profile microRNAs population of glucose-induced cardiomyoblast cell line and identify the differentially expressed microRNAs and their role under pre-diabetes and diabetes condition in vitro. Rat fetal ventricular cardiomyoblast cell line H9c2 was treated with d-glucose to mimic pre-diabetic, diabetic, and high-glucose conditions. Alteration in cellular, nuclear morphology, and change in ROS generation was analyzed through fluorescent staining. Small RNA sequencing was performed using Illumina NextSeq 550 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…There are many studies on the role of miR-503-5p in different cancers, but few studies have examined its role in DM and its related complications. In diabetic cardiomyopathy and foot syndrome, the expression of miR-503-5p is significantly upregulated 14 , 15 . Contrary to previous studies, this project shows that miR-503-5p expression is down regulated in DPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies on the role of miR-503-5p in different cancers, but few studies have examined its role in DM and its related complications. In diabetic cardiomyopathy and foot syndrome, the expression of miR-503-5p is significantly upregulated 14 , 15 . Contrary to previous studies, this project shows that miR-503-5p expression is down regulated in DPN.…”
Section: Discussionmentioning
confidence: 99%
“…miR-503-5p also plays an important role in the development of diabetic complications. In diabetic cardiomyopathy and foot syndrome, the expression of miR-503-5p is significantly upregulated 14 , 15 . In diabetic nephropathy, miR-503-5p enhances endoplasmic reticulum stress and cell apoptosis by downregulating BCL-2 16 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also associated with mitochondrial dysfunction [58]. In addition, mitochondrial dysfunction contributes greatly to age-dependent IR [59] and induces diabetic microvascular (cardiomyopathy, nephropathy, retinopathy, and neuropathy) [60][61][62][63] and macrovascular (myocardial ischemia) [64] complications. Therefore, mitochondrial quality control is a promising intervention for managing T2D and obesity.…”
Section: Mitochondrial Dysfunction In Diabetes and Obesitymentioning
confidence: 99%
“…MiRNAs are composed of approximately 22 nucleotide sequence, and regulate the expression of target genes at the post‐transcriptional levels via binding to the untranslated regions (UTRs) of complementary message RNAs 13 . Several studies have verified that the differential expression of miRNAs in myocardium are involved in DCM in either patients or animal models with DM 14–17 . Recently, we screened the expression profiles of miRNAs in myocardium from DCM mice, and found that miR‐185‐5p, one of the differentially expressed miRNAs, was markedly down‐regulated in DCM mice (Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“… 13 Several studies have verified that the differential expression of miRNAs in myocardium are involved in DCM in either patients or animal models with DM. 14 , 15 , 16 , 17 Recently, we screened the expression profiles of miRNAs in myocardium from DCM mice, and found that miR‐185‐5p, one of the differentially expressed miRNAs, was markedly down‐regulated in DCM mice (Figure 2A ). The miRNA candidate target mRNAs were predicted by miRDB database ( http://mirdb.org/miRDB/ ), and RhoA was shown to be a target gene of miR‐185‐5p, which were verified by NCBI ( http://www.ncbi.nlm.nih.gov/ ).…”
Section: Introductionmentioning
confidence: 99%